2016
DOI: 10.1007/s00586-016-4425-4
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized controlled study comparing the pain relief in patients with osteoporotic vertebral compression fractures with the use of vertebroplasty or facet blocking

Abstract: PVP produced better pain relief than FB in the short term (≤1 week). However, the difference in pain-relief between these two techniques was insignificant in the long term (follow-up between 1 month and 12 months).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 26 publications
1
39
0
1
Order By: Relevance
“…These results are consistent with the adequately powered subgroup analyses from two previous blinded RCTs3 and another trial that compared vertebroplasty to facet injections in patients with acute compression fractures 6…”
Section: Implications For Practicesupporting
confidence: 86%
“…These results are consistent with the adequately powered subgroup analyses from two previous blinded RCTs3 and another trial that compared vertebroplasty to facet injections in patients with acute compression fractures 6…”
Section: Implications For Practicesupporting
confidence: 86%
“…After literature identified and examined, all the data in this network meta-analysis were extracted from 32 trials with 2,852 subjects [Grohs et al, 2005;Pflugmacher et al, 2005;De et al, 2007;Voormolen et al, 2007;Al-Qazaz and Elshafey, 2012;Zhou et al, 2008;Buchbinder et al, 2009;R€ ollinghoff et al, 2009;Schofer et al, 2009;Bae et al, 2010;Kasperk et al, 2010;Klazen et al, 2010;Kumar et al, 2010;Movrin et al, 2010;Rousing et al, 2010;Farrokhi et al, 2011;Folman and Shabat, 2011;Blasco et al, 2012;Kallmes, 2012;Movrin, 2012;Endres and Badura, 2012;Li et al, 2012;Omidikashani et al, 2012;Van Meirhaeghe et al, 2013;Chen et al, 2014;Du et al, 2014;Kroon et al, 2014;Liu et al, 2015;Wang et al, 2015Wang et al, , 2016Clark et al, 2016;Yang et al, 2016], compared the efficacy of PKP, PVP and CT in the aspects of VAS, ODI, KA, and the occurrence of fracture, the primary traits were listed in the Table I, indicating that the average age of the patients are above 60 and large portion of them are female. Among these 32 trials, VAS was the most frequent outcome, reported by all the trials except one.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…After publications identified and checked, 27 RCTs [ 21 , 22 , 24 – 48 ] meet the inclusion criteria. The duplicate set of patients from multiple RCTs were regarded as one RCT named by the complete data and latest one or two, leaving a total of 18 RCTs [ 22 , 24 , 25 , 27 , 28 , 30 , 32 , 36 , 37 , 39 47 ] compared the efficacy of PVP, PKP, NB, and CT in the aspects of VAS. The primary traits were listed in Table 1 , indicating that a total of 1994 patients, the mean age of the patients above 60 and majority of female (551 males and 1443 females).…”
Section: Resultsmentioning
confidence: 99%